Zeolitic Imidazolate Framework-8 Membrane for H2/CO2 Separation: Experimental and Modeling - Lai, L.S. (Institute of Physics Publishing, 2018)
In this work, ZIF-8 membrane synthesized through solvent evaporation secondary seeded growth was tested for single gas permeation and binary gases separation of H2 and CO2. Subsequently, a modified mathematical modeling combining the effects of membrane and support layers was applied to represent the gas transport properties of ZIF-8 membrane. Results showed that, the membrane has exhibited H2/CO2 ideal selectivity of 5.83 and separation factor of 3.28 at 100 kPa and 303 K. Besides, the experimental results were fitted well with the simulated results by demonstrating means absolute error (MAE) values ranged from 1.13 to 3.88 for single gas permeation and 10.81 to 21.22 for binary gases separation. Based on the simulated data, most of the H2 and CO2 gas molecules have transported through the molecular pores of membrane layer, which was up to 70 . Thus, the gas transport of the gases is mainly dominated by adsorption and diffusion across the membrane. Â© Published under licence by IOP Publishing Ltd.